2007
DOI: 10.2478/s11536-007-0016-4
|View full text |Cite
|
Sign up to set email alerts
|

The impact of tourniquet on patient satisfaction in carpal tunnel decompression

Abstract: AbstractRelease of the transverse carpal ligament can be performed safely under local anesthesia and without the use of tourniquet. There are conflicting reports for the use of tourniquet in carpal tunnel syndrome. The aim of the study was to compare the patient satisfaction with and without tourniquet in patients with carpal tunnel decompression. This was a retrospective study performed in twenty-four patients who underwent bilateral carpal tunnel decompression. All the patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 8 publications
0
9
0
Order By: Relevance
“…Fan et al [14] found that postoperative pain was more severe among patients who were treated with tourniquet. Liu et al [15], Nagpal et al [16] and Saied et al [17] also reported the same finding while Nakayama and Yoshiya found no significant difference between the postoperative pain intensity of patients in tourniquet and notourniquet groups.…”
Section: Introductionmentioning
confidence: 62%
See 2 more Smart Citations
“…Fan et al [14] found that postoperative pain was more severe among patients who were treated with tourniquet. Liu et al [15], Nagpal et al [16] and Saied et al [17] also reported the same finding while Nakayama and Yoshiya found no significant difference between the postoperative pain intensity of patients in tourniquet and notourniquet groups.…”
Section: Introductionmentioning
confidence: 62%
“…For instance, Saied and Zyaei assessed the effects of tourniquet use during plate fixation of acute extraarticular tibia fractures and found that tourniquet use was associated with significantly higher levels of postoperative pain [16]. Besides, Konrad et al [33] reported that tourniquet use increased postoperative pain after open reduction and internal fixation of ankle fractures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In patients who received tourniquets, mean time with upperarm tourniquet was found as 9.5 minutes (8-11), and mean time with forearm tourniquet was 10.11 (8)(9)(10)(11)(12) minutes. A bloodless surgical area was successfully obtained with both tourniquet methods (Group 1 and 2).…”
Section: Resultsmentioning
confidence: 98%
“…Nagpal et al reported that patients were discomforted by tourniquets and there were no long-term differences in outcome with or without tourniquets [12].…”
Section: Discussionmentioning
confidence: 99%